Magnetic alignment of gamma (core)-alpha (shell) Fe2O3 nanorods in a solid polymer electrolyte for Li-Ion batteries - Schaetzl, Dean M.; Li, Peng; Chaudhari, Nilima; Bernstein, Gary H.; Fullerton-Shirey, Susan K. (Journal of Physical Chemistry C, 2014)
The temperature-dependent ionic conductivity and thermal properties are characterized for a solid polymer electrolyte of poly(ethylene oxide) (PEO) and LiClO4 filled with 1 wt % gamma-phase core (maghemite) and alpha-phase shell (hematite) Fe2O3 nanorods. Samples are solvent-cast in the absence and presence of a 0.5 T magnetic field, dried at room temperature under vacuum for 72 h, and measured under nitrogen. Vibrating sample magnetometry indicates that the magnetic treatment aligns the nanorods to some extent in the desired orientation normal to the electrode surface. For samples with an ether oxygen to lithium ratio (EO/Li) of 10:1, the nanorods induce sample-to-sample variability in the ionic conductivity. The magnetic treatment eliminates this variability, and differential scanning calorimetry data support the observation that the magnetic treatment increases the structural homogeneity of the electrolyte. For samples with an EO/Li of 3:1, the ionic conductivity is 3 orders of magnitude larger for samples containing 5 times more of the crystal structure, (PEO)(6)/LiClO4. This result is surprising because an inverse relationship between crystallinity and conductivity is normally observed for semicrystalline, solid polymer electrolytes. When the crystal fraction is increased by a factor of 8 via the combination of nanorods and magnetic treatment, the conductivity does not continue to increase, showing that the effect does not persist beyond a critical fraction of (PEO)(6)/LiClO4. The results demonstrate that field-effect alignment of magnetic nanorods increases the crystal fraction and homogeneity of PEO/LiClO4, but does not affect the ionic conductivity in the range of salt and nanorod concentrations investigated.